Pengaruh Duta Asri terhadap Sikap Peduli Lingkungan Siswa - Prani Julia Saputri; Asma Irma Setianingsih; Ilham Badaruddin Mataburu (Geography Education Study Program, Universitas Kanjuruhan Malang, 2023)
Environmental cultured school or adiwiyata is an effort to improve environmental care behavior in the world of education. SMA Negeri 30 Jakarta as an adiwiyata school formed the Duta Asri to improve the adiwiyata character of students in anticipation of the impact of environmental changes. This study aims to determine the effect of Duta Asri on students' environmental care attitudes using quantitative descriptive methods with a survey approach. The population in this study were X and XI grade students other than Duta Asri members. Sampling using simple random sampling method as many as 84 people. Data analysis using simple linear regression techniques. The results of the analysis show that there is an effect of the Duta Asri’s activities on the environmental care attitude of SMA Negeri 30 Jakarta students by 47.5%. The activities of the Duta Asri that most effect the attitude of environmental care are through information media, socialization and class hygiene competitions. The lowest activity indicator in influencing students' environmental care attitudes is listening activities. This is caused by Duta Asri do not yet have the activity of listening to descriptions, opinions and criticism from others, in this case feedback in the form of suggestions and input from students.